Theta-Modulated Head Direction Cells in the Rat Anterior Thalamus - REILLY, RICHARD; O'MARA, SHANE MICHAEL (Society of Neuroscience, 2011)
A major tool in understanding how the brain processes information is the analysis of neuronal output at each hierarchical level along the pathway of signal propagation. Theta rhythm and head directionality are the two main signals found across all levels of Papez's circuit, which supports episodic memory formation. Here, we provide evidence that the functional interaction between both signals occurs at a subcortical level. We show that there is population of head direction cells (39%) in rat anteroventral thalamic nucleus that exhibit rhythmic spiking in the theta range. This class of units, termed HD-by-theta (head direction-by-theta) cells, discharged predominantly in spike trains at theta frequency (6?12 Hz). The highest degree of theta rhythmicity was evident when the animal was heading/facing in the preferred direction, expressed by the Gaussian peak of the directional tuning curve. The theta-rhythmic mode of spiking was closely related to the firing activity of local theta-bursting cells. We also found that 32% of anteroventral theta-bursting cells displayed a head-directional modulation of their spiking. This crossover between theta and head-directional signals indicates that anterior thalamus integrates information related to heading and movement, and may therefore actively modulate hippocampo-dencephalic information processing.
PUBLISHED
Keywords: Neuroscience; Theta rhythm